Memórias de uma revolta esquecida: o Baixo-Amazonas na revolução constitucionalista de 1932 - OLIVEIRA, Walter Pinto de (Universidade Federal do Pará, 2014)
The purpose of this dissertation is to discuss the establishment of the first armed movement in reaction to the Tenentismo and to the provisional government in the extreme north, materialized in a civilian and military rebellion, led by sergeants of a small army unit in the city of Óbidos, country of Amazônia, in 1932, with the aim of analyze their meanings, subjects experiences, fight strategies and the relation between the rebellion and the Constitutionalist Revolution of São Paulo. Eighty years after, the event, that had a tragic ending in the naval battle of Itacoatiara, remains as one of the most unknown in the history of Brasil. In search for answer, this dissertation investigates the official discourse of the paraense interventor which invalidates the legitimacy of the rebellion action and its reflection in the society at the time.